Solidaritatea socială – tendință constantă a constituționalismului [Articol] - Guceac, Ion (Artpoligraf, 2021)
The purpose of this study is determined by the idea of social cooperation and solidarity in the conditions of contemporary constitutionalism, where the state must evolve as an instrument of consent and social compromise, ensuring the formation of a balance of diversity of private and collective interests in society. Starting from the fact that any constitution must ensure the balance between the values of freedom and the mutual responsibility of the citizen and the state, it is recommended to include in the normative content of the Constitution of the Republic of Moldova. provisions on social solidarity and ways to ensure it.
SOCIAL SOLIDARITY – A CONSTANT TREND OF CONSTITUTIONALISM
Keywords: constitutionalism; social solidarity